THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION: EVIDENCE FROM PUBLIC HOSPITALS - Alshatnaw, Hamza Ali Mohammad; Amlus, Mohd Harith Bin (International Journal For Research In Business, Management And Accounting, 2016)
This paper sought to assess and analyze customer satisfaction with service quality (Tangible, Reliability, Responsiveness, Assurance and Empathy), in the public hospitals in Jordan. Specifically, it examined the determinants of satisfaction and the effects of customer satisfaction in Jordan’s public hospitals. The study was a cross-sectional survey that used self-administered structured questionnaire to the target population of customers of universities (Yarmouk University and Jordan University of Science and Technology, JUST) employees who they visit the two public hospitals (King Abdullah Hospital and Princess Basma Hospital) in Jordan. Out of the two hundred and forty- two questionnaire administered, 242 usable questionnaires were obtained constituting 93% for analysis. SPSS software package version 19.0 to test the descriptive analysis and reliability, and Structural Equation Modeling (SEM) which is Analysis